Cutaneous Epithelioid Clear Cells Angiosarcoma in a Young Woman with Congenital Lymphedema - Tabareau-Delalande, Flore (Hindawi Publishing Corporation, 2013)
Angiosarcomas are rare aggressive neoplasms that can occur secondary to chronic lymphedema (Stewart-Treves syndrome). Although secondary angiosarcomas are commonly described after-mastectomy and/or after-radiotherapy, few cases have been reported in association with chronic lymphedema of congenital origin. We report the clinical, pathological, and cytogenetic findings in a case of cutaneous epithelioid clear cells angiosarcoma that occurred in a 21-year-old woman with hemibody congenital lymphedema. Surgical biopsies of the tumor mass revealed diffuse epithelioid proliferation of clear atypical cells, for which immunophenotyping highlighted the vascular differentiation. Despite en bloc resection of the tumor, the patient died of metastatic disease three months after diagnosis. This case illustrates the clinical and pathology characteristics of angiosarcoma that is a rare entity secondary to chronic lymphedema. It is the first reported case for which the c-MYC amplification status was assessed. The diagnostic value of this amplification should be further evaluated in this specific context.